Grupa wsparcia jako przykład pomocy członkom rodzin osób z demencją - Gwiżdż, Michał (Kultura-Społeczeństwo-Edukacja, 2023)
With the rapid increase in the diagnoses of diseases leading to dementia, the number of individuals providing informal care to those diagnosed with such diseases is on the rise. Caregivers of people with dementia are exposed to an elevated risk of experiencing loss, chronic stress, effort, and suffering, as well as a decreased quality of life. The greatest burden on the relatives of those affected is evident in the area of mental health. Caregivers are often referred to as “invisible patients”. This article presents the concept of a support group as a form of assistance for informal caregivers of dementia patients. It also discusses the formal characteristics of this form of assistance. The article outlines the goals, possibilities, and limitations of support groups compared to other forms of caregiver support. Furthermore, it discusses the basic rules and functioning styles of a support group, giving it a stable structure. Finally, the most common issues that arise in meetings led by the author of this article are presented, distinguishing between emotional conflicts and practical problems. The conclusion provides practical guidance for the moderator (facilitator) to enhance the effectiveness of the meetings. The methodological basis is the author’s own experience in running a support group for informal caregivers in the years 2003–2019 in Krakow.